Pengaruh Content Marketing, Endorsement Review dan Customer Rating terhadap Minat Beli Produk Glad2Glow pada E-Commerce Tiktok Shop : (Studi pada Mahasiswa Universitas Muhadi Setaibudi) - Salsa Ainurrohmah; Andi Yulianto; Nur Khojin; Syariefful Ikhwan; Roby Setiadi (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
The rapid growth of e-commerce, particularly through the TikTok Shop platform, has created new dynamics in consumer behavior and presented challenges for businesses in understanding the factors that influence purchase intention, especially among young people who are the most active social media users. This study aims to explore in greater depth the effects of content marketing, endorsement reviews, and customer ratings on purchase intention for Glad2Glow products on TikTok Shop. The research employed a quantitative approach using a survey method involving 180 active students from Universitas Muhadi Setiabudi as respondents. A random sampling technique was applied to ensure the representativeness of the sample, while the research instrument consisted of a questionnaire using a Likert scale ranging from 1 to 10. Data analysis was conducted using multiple linear regression to test the influence of each independent variable on the dependent variable. The findings indicate that, when tested partially, only content marketing had a significant effect on purchase intention, with a significance value of 0.000 (< 0.05), whereas endorsement reviews and customer ratings did not show a significant effect. However, when tested simultaneously, the three variables—content marketing, endorsement reviews, and customer ratings—collectively influenced purchase intention in a significant manner. These results emphasize that content marketing strategies play a crucial role in shaping consumer purchase intention, particularly for local beauty products marketed on interactive digital platforms such as TikTok Shop. The study provides practical implications for businesses to prioritize creative, consistent, and relevant content marketing strategies to enhance product attractiveness and strengthen brand positioning in the competitive beauty industry.